Atypical maternal interaction is associated with elevated levels of hair cortisol in children - Köhler-Dauner, Franziska; Mayer, Inka; Hitzler, Melissa; Karabatsiakis, Alexander; Matits, Lynn; Bach, Alexandra M.; Rost, Katharina; Fegert, Jörg M.; Kolassa, Iris-Tatjana; Ziegenhain, Ute (Frontiers in Pediatrics, 2023)
The quality of maternal caregiving is an important factor in the healthy development of a child. One consequence of prolonged insensitive and atypical maternal interaction behavior (e.g. withdrawing from interactions with the child and role-reversal, i.e the takeover of the parental role or parts of it by the child) in mother-child-dyads can cause alteration of the child’s stress response system. Higher salivary cortisol concentrations were reported in infants and toddlers directly after negative interactions with their parents. However, no study to date has examined the association between atypical maternal interaction behavior and hair cortisol concentrations (HCC) in infants. Here, we studied the association of maternal interaction behavior with HCC of the child. Mother-child dyads (N=112) participated in the longitudinal study My Childhood – Your Childhood. The AMBIANCE scale and its subscales were used to assess atypical maternal interaction behavior during the Strange Situation Procedure. Chronic stress levels in the child were assessed by HCC of 3 cm hair strands at the age of 12 months. Maternal educational level (operationalized in highest education level) served as a control variable. Robust multiple linear regression analyses revealed that role/boundary confusion was associated with HCC, i.e. the higher atypical interaction behavior of the mother the higher the HCC in the children. By measuring hair cortisol in this study, it is possible to determine the average long-term activity of the child’s stress response system.Thus, atypical maternal interaction behavior could be a risk factor for persistent stress in children, contributing to a higher risk for negative health outcomes in later life. The results of this study highlight the importance of early intervention programs that focus on the relationship between mother and child.